PENGARUH CITRA MEREK, KESADARAN MEREK DAN E-WOM TERHADAP MINAT BELI OBAT JAMU MASUK ANGIN BEJO JAHE MERAH DI INDONESIA - Christarevy Renaputra Hosfiar, (2021)
This study analyzed the buying interest in the herbal cold remedy of BEJO Ginger Red in Indonesia. BEJO Red Ginger is a herbal cold remedy using red ginger which is produced to nourish or maintain her immune system, including the herbal cold medicine. This study aims to understand the things that influence the buying interest of Red Ginger Bejo in Indonesia. This research includes the influence of brand image, brand awareness and e-word of mouth. Descriptive and inferential approaches are used in this study. Researchers used data types in the form of quantitative data and used primary and secondary data sources. 385 people involved in this study as a sample, who are consumers of BEJO Ginger Red using convenience sampling technique. Data were collected using an e-questionnaire (google form) which is distributed online through social networks. The data analysis technique was processed using Partial Least Square (PLS). The results of data analysis show that: (1) Brand image has a significant effect on Purchase Intention of Bejo Ginger Red Medicine (2) Brand awareness has no significant effect on Purchase Intention of Bejo Jahe Merah Jamu (3) E-WOM has no significant effect on Purchase Intention Red Ginger Bejo Herbal Medicine.